Bacterial suppressor-of-copper-sensitivity proteins exhibit diverse thiol-disulfide oxidoreductase cellular functions - Yaoqin Hong; Jilong Qin; Lachlan Mitchell; Jason J. Paxman; Begoña Heras; Makrina Totsika (iScience)
Summary: Disulfide bond (Dsb) oxidoreductases involved in oxidative protein folding govern bacterial survival and virulence. Over the past decade, oligomerization has emerged as a potential factor that dictates oxidoreductase activities. To investigate the role of oligomerization, we studied three Dsb-like ScsC oxidoreductases involved in copper resistance: the monomeric Salmonella enterica StScsC, and the trimeric Proteus mirabilis PmScsC and Caulobacter crescentus CcScsC. For copper sequestration, ScsC proteins must remain in the reduced form. However, all three ScsC proteins exhibit both dithiol oxidation and disulfide reduction activity, despite structural differences and previously reported limited in vitro activity. Most ScsC reductase activity relies on interactions with E. coli DsbD reductase, while oxidase activity depends on environmental oxidation. Interestingly, engineered monomeric PmScsC interacts effectively with the E. coli DsbB oxidase, at the partial expense of its reductase activity. These findings highlight oligomerization of oxidoreductases as a steric hindrance strategy to block undesirable upstream oxidative interactions.